Changes in Rats’ Gut Microbiota Composition Caused by Induced Chronic Myocardial Infarction Lead to Depression-Like Behavior - Wang, Qianwen; Wang, Xi; Lv, Yong; Yang, Chun; Zhou, Chenliang; Wang, Long (Frontiers in Microbiology, 2022)
Depression is common among patients who have chronic myocardial infarction (CMI). Despite their frequency, depression and CMI are bidirectional related conditions, risks are for each other, and they often co-exist, suggesting shared or interacting pathomechanisms. Accumulating data revealed the effects of gut microbiota in terms of regulating depression via the gut–brain axis. Thus, we investigated the role of gut microbial dysbiosis in CMI-induced depression-like behavior and the potential underlying mechanisms. Hierarchical cluster analysis of sucrose preference test (SPT) results was adopted to classify the CMI rats into depression-like behavior (Dep) or non-depression-like behavior (Non-Dep) phenotypes. First, 16S ribosomal RNA sequencing analysis showed both β-diversity and relative abundance of several gut bacteria significantly differed between the Dep and Non-Dep rats. Next, transplantation of fecal microbiota from Dep rats visibly altered the relative abundance of gut microbiota and also induced depression-like behavior in the antibiotics-treated pseudo-germ-free rats. In conclusion, these findings suggest that abnormal gut microbiota composition contributes to the onset of CMI-induced depression-like behavior and that exogenous regulation of gut microbiota composition is a potential therapeutic strategy for CMI and related depression-like behavior.